EVALUASI DAN EFEKTIFITAS ALOKASI DANA DESA (ADD) DALAM PENGURANGAN KEMISKINAN DI KABUPATEN BENER MERIAH - Bismi Inayatsyah; Teuku Zulham (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract The Central Government is seriously concerned with equitable development from the village level, specifically those listed in the State Budget (APBN) that gave birth to a program, namely village funds. The purpose of this study is to determine the effectiveness of allocating village funds to poverty in Bener Meriah Regency. The analytical method used is descriptive analysis, namely research that uses data collection methods obtained directly from respondents through interviews, and uses Simple Linear Regression Analysis using the SPSS Model. The results of the study indicate that the management of village funds in Bener Meriah Regency is still not optimal to be able to reduce poverty. Infrastructure development is the main thing that must be focused on in order to create easy and affordable access that can be seen from the help of village needs which leads to increased village income and reducing poverty.Keywords:Village funds, effectiveness, poverty, allocation.